Digital Transformation and Innovation Management: A Synthesis of Existing Research and an Agenda for Future Studies. Issue 1 (27th January 2021) - Appio, Francesco Paolo; Frattini, Federico; Petruzzelli, Antonio Messeni; Neirotti, Paolo
Abstract: Management and organizational scholars have paid increasing attention to the interconnections between digital transformation and innovation management in the last decade. However, a highly fragmented understanding of this topic is what we are left with so far. In this editorial, we suggest an approach to open up the black box of the interplay between digital transformation and innovation management by providing a framework that identifies three levels of analyisis (i.e., macro, meso, and micro) along which existing and future research on the topic can be organized. This model encourages scholars to conduct theoretical and empirical studies on how digital transformation affects ecosystems' structure and governance, how industries and firms compete and organize for innovation in a digitalized world, how the processes for developing new products and services change under the effect of digital technologies, and the implications of digital transformation on managing people and teams involved in the innovation process, among the other topics. We also provide a synthesis of the eight papers published in the Special Issue that this editorial introduces and develop an agenda for future research that will hopefully contribute to encourage and shape future scholarly efforts into this field.